Dynamic Relations between Stock Price and Exchange Rate: Evidence from South Asia - Ali, Mostafa; Sun, Gang (International Journal of Economics and Financial Issues, 2017)
Our study strives to explore the dynamic association between stock price and foreign exchange rate by taking daily data for a period of January 1, 2009 to June 30, 2015. We employ Bivariate Vector Auto regression (VAR) Model as well as Vector Error Correction Model (VECM) to discover the short run and long run relationship between these two financial variables. We fail to uncover any short run or long run association between these two financial variables for Bangladesh but identify a unilateral causal relationship running from stock price to exchange rate in Pakistan. Moreover, we find a long run negative relation that leads from exchange rate to stock price and a short run unidirectional causal linkage running from stock price to exchange rate in India. Granger causality test results confirmed these findings. The empirical findings of the study do not provide any precise evident in favor of Portfolio hypothesis or Goods market hypothesis but a mixed interaction of all theories. Keywords: Dynamic relations, Stock price, Exchange rate, Vector Error Correction Model (VECM) JEL Classifications: C32, E44, F31, G15